Cyto-histological correlation of salivary gland lesions according to the Milan reporting system - Hamid, Shireen; Mudassar, Muhammad; Hamid, Nida; Zia, Muhammad Sarwar; Mehmood, Tariq; Hameed, Sadia (Journal of Rawalpindi Medical College, 2024)
Objective: The objective of this study is to correlate FNAC outcomes according to the Milan Salivary Gland Cytology Reporting System (MSRSGC)system with histopathological findings of salivary gland lesions, taking as the gold standard. Study Design: Descriptive Retrospective study. Setting: Private lab in Faisalabad, Pakistan. Period: January 2017 to December 2022. Material and Methods: We assessed cytology aspirates from salivary gland lesions in individuals of both genders. Demographic details, including age, gender, lesion location, and duration, were systematically recorded. The cytology cases without subsequent histopathology were excluded from the study. The cytology cases were categorized based on the Milan Salivary Gland Cytology Reporting System (MSRSGC): nondiagnostic, non-neoplastic, benign, or, salivary gland tumor of unknown malignant potential (SUMP), suspicious for malignancy, or malignant. The sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy of FNAC were calculated. The data was analyzed using SPSS 24 taking a P value < 0.05 as significant Results: This study evaluated 74 cases of salivary gland lesions with cytology, all of which underwent histopathology. These cases included 32 (43.2%) women and 42 (56.8%) men with an average age of 42 years. The right side is more affected (52.7%) than the left side (47.3%). The most common salivary gland was the parotid gland in 61.9 % of cases. According to the Milan system, the majority of cases were classified as benign category IVa (58.1%), followed by cases in categories II, V, and VI (14.9%, 6.8%, and 12.2%) respectively. While cases in category III and IV b (4.1 %). The FNAC correlation with histopathology showed a sensitivity of 95.2 % and a specificity of 71.7%. The positive predictive value is 77.6 %, and the negative predictive value is 93.5 %. The diagnostic accuracy of FNAC was determined to be 95.2% compared to the final histopathological diagnosis. Correspondingly, the associated risk of malignancy for these categories was 0%, 30%, 0%, 30%, 100%, and 100%, respectively. Conclusion: The overall diagnostic accuracy of cytological reporting of salivary gland lesions according to the Milan nomenclature was 83.6 %. These findings showed the significant contribution of MSRSGC in accurately diagnosing malignant lesions, aiding clinicians in making well-informed decisions regarding specific treatment strategies. Keywords: Fine needle aspiration cytology (FNAC), Milan salivary gland cytology reporting system (MSRSGC), histopathology, salivary glands.